The Presentation and Treatment of Collocations as Secondary Guiding Elements in Dictionaries - Gouws, Rufus H. (Lexikos, 2015)
Collocations represent an item type that is frequently presented and treated in an insufficient way in dictionaries. It is cumbersome for the user to distinguish between collocations and example sentences, and dictionaries often include no additional treatment directed exclusively at collocations. In this contribution the need is shown for the recognition of collocations as an item type. It is suggested that they should be presented in such a way in dictionary articles that they can function as secondary guiding elements. Besides their inclusion in dictionaries collocations also need to receive a treatment that makes provision for, in many instances, at least an example sentence but that could also include, when necessary, stylistic and other labels and even a brief paraphrase of meaning. It is shown how collocations are presented and treated in a few existing dictionaries. These presentations are criticised and proposals are made for an improved presentation. In this regard Wiegand's model for a semi-integrated microstructure is adapted to provide for the presentation of collocations in their own non-integrated search zone. Besides the explicit presentation of single collocations proposals are made for an implicit presentation of complex collocations. From a single item form users should then be able to retrieve different items. Although the discussion primarily focuses on printed dictionaries proposals are also made for the presentation of collocations in online dictionaries.